Mapping Marginalised Temporalities: A Chronotopic Reading of Neel Mukherjee’s A State of Freedom - Neelu Jain, Vijendra Singh (European Economic Letters (EEL), 2025)
Within the framework of the chronotope of Bakhtin, this paper explores Neel Mukherjee’s A State of Freedom, focusing on the metaphorical interplay of the junkyard (the concealed, marginalised past) and the foreyard (the apparent, normative present). The multicultural characters featured in the novel (both the city elites and migrants living in the country) and its disordered plot structure create a literary space in which different temporalities and spatialities intersect. These crossroads are glimpses of synchronicity, the moments when the past and the present, the center and the periphery, the tradition and modernity can be united and reveal their interdependence. Applying the concept of chronotope presented by Bakhtin, where the spatial and the temporal are merged into a solid artistic form, this analysis shows how A State of Freedom establishes the opposition between the two realms of the consumer-infused foreyard and the memory-laden junkyard that remains mostly unseen. The villages, urban apartments, and building sites in which the book takes place are significant settings where personal and social histories merge and become concrete, not mere picturesque backdrops. Using flashbacks, shifting views and switching between social and physical worlds, the story by Mukherjee exposes the issues of erasure. This provides an emphasis on difference and going back to the backyard as a repository of lost knowledge and lifestyles. In conclusion, the author claims that in A State of Freedom, there is an intensive reflection on the concomitancy and disassociation of time and space in modern India, which demonstrates that the elements of synchronicity can be used to enhance the inhumanity of marginalisation and the alternative of salvation.